Analisis dan Perancangan (E-Raport) Berbasis Web dengan Metode Prototype (Studi Kasus SMAN 9 Tangerang Selatan) - Fauzan Azhima Fil Ramadhan; Muhammad Yunus Rangkuti (CV. Multi Kreasi Media, 2025)
SMA Negeri 9 Kota Tangerang Selatan is an ICT-based model school. In the academic process, especially the assessment still uses Microsoft Excel to store data, so that it can cause data redundancy and human errors, as well as provide delays in information to students / guardians of students. The purpose of this study is to design an academic system in processing the necessary assessment data according to the needs of students and schools, the author tries to make